2021
DOI: 10.1038/s41598-021-03428-z
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of easy separable and reusable MIL-125(Ti)/MIL-53(Fe) binary MOF/CNT/Alginate composite microbeads for tetracycline removal from water bodies

Abstract: In this investigation, we aimed to fabricate easy separable composite microbeads for efficient adsorption of tetracycline (TC) drug. MIL-125(Ti)/MIL-53(Fe) binary metal organic framework (MOF) was synthetized and incorporated with carbon nanotube (CNT) into alginate (Alg) microbeads to form MIL-125(Ti)/MIL-53(Fe)/CNT@Alg composite microbeads. Various tools including FTIR, XRD, SEM, BET, Zeta potential and XPS were applied to characterize the composite microbeads. It was found that the specific surface area of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(30 citation statements)
references
References 74 publications
0
27
0
Order By: Relevance
“…Regarding FTIR spectrum of CA, the absorption peaks at 1031 and 1733 cm −1 are attributed to C–O, C=O, while the two peaks located at 1367 and 1220 cm −1 are ascribed to O=C–OR and C–O–C of the pyranose ring, respectively 47 . In addition, the peaks at 1490, 2940 and 3478 cm −1 are assigned to C–H, aliphatic CH 2 and O–H groups, respectively 48 , 49 . Finally, the FTIR spectrum of SGO@CA beads shows the main characteristic peaks of SGO and CA asserting the good combination between SGO and CA and the successful fabrication of the SGO@CA beads.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding FTIR spectrum of CA, the absorption peaks at 1031 and 1733 cm −1 are attributed to C–O, C=O, while the two peaks located at 1367 and 1220 cm −1 are ascribed to O=C–OR and C–O–C of the pyranose ring, respectively 47 . In addition, the peaks at 1490, 2940 and 3478 cm −1 are assigned to C–H, aliphatic CH 2 and O–H groups, respectively 48 , 49 . Finally, the FTIR spectrum of SGO@CA beads shows the main characteristic peaks of SGO and CA asserting the good combination between SGO and CA and the successful fabrication of the SGO@CA beads.…”
Section: Resultsmentioning
confidence: 99%
“…It was concluded that MgO provided more active sites which agrees with Lihua et al 91 One of the difficulties of phosphate removal is its presence in multiple forms where it exists as H 3 PO 4 (pH < 2), H 2 PO 4 À (pH 2-7), HPO 4 2À (pH 7-11), and PO 4 3À (pH > 11). Alg-MgO@BT showed a high adsorption capacity towards phosphate ions over a wide pH range (3)(4)(5)(6)(7)(8)(9)(10) where the phosphate removal efficiency exceeded 99% at a pH lower than 7. This may be anticipated from the strong electrostatic interaction between H 2 PO 4 À and HPO 4 2À species and the positively charged Alg-MgO@BT.…”
Section: Clay-modied Alginatementioning
confidence: 99%
“…In addition, the human body cannot survive without water for over three days. Although we all have to be conscious of the imperative need for water conservation, [1][2][3][4][5] the aggravation of water pollution has grown day by day. [6][7][8][9] This catastrophic problem results from the disposal of numerous pollutants into water bodies, 10,11 particularly phosphate owing to its presence in nature and excessive uses in various elds.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray diffraction (XRD) analysis is an indispensable step in gaining information about the nanomaterials' crystal structure and crystal lattice. 41,42 The XRD spectrum of the pristine biochar (Figure S1a) exhibited characteristic peaks at 28.5, 40.6, and 50.26°, which were indexed to the (002), (100), and (004) planes, respectively, as previously mentioned by other workers, 43 whereas the XRD pattern of the Ag@biochar composite (Figure S1b) demonstrated the same peaks of the pristine biochar yet with a lower intensity and other new peaks at 32.1, 46.06, and 62.5°which were indexed to the (111), (200), and (220) planes, respectively, referring to face-centered-cubic silver (JCPDS file number 04-0783). Moreover, the (111) plane, in accordance with many workers, 44 was the preferred growth direction for the phytosynthesized Ag@biochar nanocomposite.…”
Section: Resultsmentioning
confidence: 99%